Chances and Limitations of Video Games in the Fight against Childhood Obesity—A Systematic Review. (3rd May 2017) - Mack, Isabelle; Bayer, Carolin; Schäffeler, Norbert; Reiband, Nadine; Brölz, Ellen; Zurstiege, Guido; Fernandez‐Aranda, Fernando; Gawrilow, Caterina; Zipfel, Stephan
Abstract: Objective and Method: A systematic literature search was conducted to assess the chances and limitations of video games to combat and prevent childhood obesity. This search included studies with video or computer games targeting nutrition, physical activity and obesity for children between 7 and 15 years of age. Results: The study distinguished between games that aimed to (i) improve knowledge about nutrition, eating habits and exercise; (ii) increase physical activity; or (iii) combine both approaches. Overall, the games were well accepted. On a qualitative level, most studies reported positive effects on obesity‐related outcomes (improvement of weight‐related parameters, physical activity or dietary behaviour/knowledge). However, the observed effects were small. The games did not address psychosocial aspects. Conclusions: Using video games for weight management exclusively does not deliver satisfying results. Video games as an additional guided component of prevention and treatment programs have the potential to increase compliance and thus enhance treatment outcome. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.